A commentary on "Ghirlandetta": two narrative strategies (inOpera Esercizi di lettura su testi contemporanei, 2024)
The paper offers a close reading of Ghirlandetta – the central section of Giovanni Giudici’s Lume dei tuoi misteri – focusing on two narrative strategies adopted by the poet: 1) the intentional misdirection of the reader, with the goal of bringing him closer to the characters; 2) the female character’s rewriting of events in her favour. Because of the chosen focus, only some poems are selected for this analysis. After a brief contextualization of Ghirlandetta between the other sections, the two narrative techniques are clarified and illustrated through the commentary of the singular texts. The author’s unpublished textual variations belonging to Rodolfo Zucco’s archive are mentioned when needed.
Keywords: Commentary; Narrative Strategies; Textual Variations; Lume dei tuoi misteri; Giudici